Prevalence of juvenile osteoarthritis tarsal joints in overweight crioulo breed mares in extensive nutritional management (Research, Society and Development, 2021)
Breeders look for effective nutritional management, but, behind it, this management causes horses with signs of overweight between different ages. Obesity is mentioned in several horses breeding as the cause of numerous orthopedic problems such as laminitis, osteochondritis dissecans and juvenile osteoarthritis. The aims of this research is to evaluate, through radiographic examination, signs of possible osteoarticular disease in tarsal joints of overweight Crioulo females, which was foaled and bred at a particular farm in extensive management. A retrospective cohort study was performed out at field conditions with overweight and/or obese equine females, from birth until adulthood. It was evaluated thirty-seven Crioulo females, which were foaled and bred at the same particular farm. All animals were weighed measured with a scale tape and the fat tailhead was measured through ultrasound examination. The radiographic projections of the tarsal joints region were realized in both pelvic limbs. Crioulo females presented average body condition score (BCS) of 8; average body weight of 557,29 kg; average fat tailhead of 30,54 +3,17 mm. About of 62,16% of the total females were radiological characterized in having decreased of the articular space, bone proliferation and articular osteophytes of the tarsal joints. Those articular changes were classified as grade 1, 2, 3 or 4, according to the severity. Articular changes in the tarsal joint were observed in 70% of 12’ months aged fillies. Both, mares’ obesity and growing fillies’ overweight, can be an important ethiological factor to the development of tarsal articular diseases in the Crioulo breed.